2004
DOI: 10.1074/jbc.m314000200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and Dioxygen Binding to the Endospore Coat Laccase from Bacillus subtilis

Abstract: The CotA laccase from the endospore coat of Bacillus subtilis has been crystallized in the presence of the noncatalytic co-oxidant 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonate) (ABTS), and the structure was determined using synchrotron radiation. The binding site for this adduct is well defined and indicates how ABTS, in conjunction with laccases, could act as an oxidative mediator toward non-phenolic moieties. In addition, a dioxygen moiety is clearly defined within the solvent channel oriented toward one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
82
2
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(99 citation statements)
references
References 30 publications
7
82
2
8
Order By: Relevance
“…Low-error-rate (0 to 4 mutations/kb) mutagenesis was used for introducing random mutations in the 816-bp segment of the lcc gene from C. bulleri. This segment was toward the C-terminal region and is proposed to contain the catalytic Cu centers and putative substrate-binding sites (34). The C-terminal region of both ascomycete and basidiomycete laccase is reported to influence the catalytic property of laccase (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Low-error-rate (0 to 4 mutations/kb) mutagenesis was used for introducing random mutations in the 816-bp segment of the lcc gene from C. bulleri. This segment was toward the C-terminal region and is proposed to contain the catalytic Cu centers and putative substrate-binding sites (34). The C-terminal region of both ascomycete and basidiomycete laccase is reported to influence the catalytic property of laccase (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The darker red tone of the concentrate compared to the filtrate fraction suggests a relative enrichment of the red derivatives (bound in complexes?) with high-MW compounds and especially an adduct constellation with (enzyme) proteins [30,65,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that Asp501 in B. subtilis laccase lies at the surface of the water channel by which the dioxygen molecule approaches the trinuclear copper center. It also is involved in the formation of hydrogen bonds with the solvent molecules in the channel [14]. Multiple sequence alignments showed that Asp501 has only been found in laccases from Bacillus sp., whereas a glycine residue at the corresponding position existed in other bacterial and fungal laccases ( Figure S2).…”
Section: Introductionmentioning
confidence: 99%